Dimensional variation of axial tracheids along the stem of Sequoia sempervirens Endl (Lamb.) - Müller, Bruna Verediana; Nisgoski, Silvana; Muniz, Graciela Ines Bolzon de; Cunha, Alexsandro Bayestorff da; Oliveira, Joanna Rebelo de; Andreolla, Veruschka Rocha Medeiros (Scientia Agraria Paranaensis, 2017)
The present study aimed to evaluate the dimensional variation of axial tracheids along the stem of Sequoia sempervirens Endl (Lamb.). Three trees with approximately 18 years old were selected, from which six discs were removed from along the height. Of each disk, three samples were taken from the vascular cambium to the medulla. For each sample we proceeded to measure the individual characteristics of tracheids. As a procedure of analyzing the results, we applied the Tukey test at 5% probability of error. The results showed that of the dimensions evaluated for the axial tracheids of S. sempervirens, only the length showed a significant variation pattern, increasing in the direction from the medulla to the vascular cambium and along the height of the trees. Also, it was verified that the cell wall thickness of the axial tracheids of S. sempervirens is superior to that found in the literature for species of gymnosperms group.